NOTARIES AND THE DIGITAL ERA: VALIDITY OF ELECTRONIC DEEDS AND LEGAL PROTECTION IN INDONESIAN LAW - Ami Raditya; Dodi Jaya Wardana; Intan Inayatun Soeparna; Faizal Kurniawan; Ghansham Anand; Mohammad Reevany Bustami (KANUN:JURNAL ILMU HUKUM, 2025)
The advancement of information technology has driven significant transformations in legal practice, particularly in the implementation of notarial authority. A central issue arising from these developments concerns validity of electronic deeds and the guarantee of legal protection for the parties utilizing them. This article critically examined the validity of electronic deeds from the perspective of Indonesian positive law, with specific reference to Law Number 2 of 2014 concerning the Position of Notary (UUJN); and the legal protection for parties in civil legal relations expressed through electronic deeds. Employing a normative juridical methodology, this article integrated both statutory and conceptual approaches. The results of the analysis revealed that although the Law on the Position of Notary still emphasized the form of authentic deeds in writing and physically signed, regulatory developments in the field of information technology, particularly Law Number 11 of 2008 concerning Electronic Information and Transactions and its amendments, have opened up space for the recognition of electronic documents and signatures as valid evidence. However, inconsistencies between these regulations and the norms in the UUJN, thus raising doubts regarding the legality of electronic deeds as authentic deeds. Moreover, ensuring legal protection for parties using electronic deeds must be ensured by guaranteeing the authenticity, integrity, and confidentiality of electronic documents. Consequently, notaries, as public officials, are required to adapt their authority to technological developments, including the use of certified electronic signatures, digital security systems, and online verification mechanisms.